Molecular Characterization of Human Cryptosporidium Isolates from in Kirkuk, Iraq - Rasheed, Inas I.; Hasan, Hussein F.; Ahmed, Neama A. (Iraqi Journal of Science, 2025)
This investigation aimed to determine the prevalence of Cryptosporidium in children residing in Kirkuk, Iraq. DNA was extracted from 64 stool samples that had tested positive for Cryptosporidium oocysts via microscopic examination. The extracted DNA was then analyzed using 18S ribosomal RNA (rRNA) gene polymerase chain reaction (PCR) testing. Significant differences were found in the prevalence of parasite in rural community (65.6%) compared to urban community (14.17%). Whereas, non-significant differences were observed in the rate of  infectivity in male (50%) as compared to (29.7%) in female. The results also revealed significant differences between infectivity rate and age groups (P=0.004). In contrast, the use of the PCR system demonstrated that this technique is a more specific and sensitive method for the detection and identification of protozoan parasites like Cryptosporidium. Overall, the results confirmed that C.Parvum was frequently the species demonstrated in Kirkuk.